Bersih : pendirian PAS. (Kuala Lumpur : Penerbit Unit Buku Harakah, 2012)
Statement of Parti Islam Semalaysia or Islamic Party of Malaysia in supporting Bersih, a coalition of NGOs which seeks to reform the current electoral system in Malaysia.
Keywords: Parti Islam SeMalaysia; Riots -- Malaysia; Demonstrations -- Malaysia